The Beginning of Ottoman-Brazilian Relations and the Visit of Brazilian Emperor Dom Pedro II and his Wife Empress Teresa Cristina to the Ottoman Empire and the Holy Lands [1876] - Selim Hilmi Özkan (Türkiyat Mecmuası)
Ottoman-Brazilian relations began in the mid-19th century. After this process, diplomatic representations and mutual political and commercial relations were established. Immediately after the start of Ottoman-Brazilian political and commercial relations, there was a significant wave of migration from Ottoman territories, mainly from Syria and Mount Lebanon to Brazil. During this migration wave, Brazilian Emperor Dom Pedro II and his wife, Empress Teresa Cristina, unofficially visited the Ottoman Empire and the Holy Lands in October 1876. The most important reason for the visit is to visit the holy places in and around Jerusalem, which are considered sacred by the three divine religions of the emperor and his wife. Although the visit was unofficial, it was closely monitored by the Ottoman administration and Sultan Abdulhamid II. The king and queen returned to their country quite pleased with the Ottoman rulers’ visits and attention. In this study, the purpose, impact, and consequences of this visit, which is thought to have had a significant influence on migration from Ottoman territories to Brazil, have been attempted to be elucidated. Our study’s primary sources consist of documents classified under various funds in the Ottoman Archives in Turkey, documents found in the Museu da Imigração do Estado de São Paulo in Brazil, and libraries in the United States of America. In addition, direct and indirect studies on the visit have also been conducted. In our study, the document examination method, which is an indispensable method in historical research, was preferred.